2004
DOI: 10.1021/jo035791c
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Oxidative Coupling of 4-Hydroxystilbenes:  Synthesis of Resveratrol and ε-Viniferin (E)-Dehydrodimers

Abstract: Treatment of 5-[2-(4-hydroxyphenyl)vinyl]benzene-1,3-diol (resveratrol) with an equimolar amount of silver(I) acetate in dry MeOH at 50 degrees C for 1 h followed by chromatographic purification with a short silica gel column allowed the isolation of its (E)-dehydrodimer, 5-[5-[2-(3,5-dihydroxyphenyl)vinyl]-2-(4-hydroxyphenyl)-2,3-dihydrobenzofuran-3-yl]benzene-1,3-diol, as a racemic mixture in high yield. The present method was applicable to the oxidative dimerization of 4-hydroxystilbenes such as trans-styry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 14 publications
2
77
1
2
Order By: Relevance
“…The results of these two experiments clearly supported our hypothesis that the reaction proceeded through radical-radical coupling and not through the radical addition to the double bond of a non-radical substrate. These results were in accordance with most of the literature reports [8,9] and not with the hypothesis suggested by Penning and co-workers, who proposed a mechanism in which the resveratrol dimerization occurs via radical attack to a second molecule of resveratrol. [14] …”
Section: Substrate (Mg)supporting
confidence: 92%
See 2 more Smart Citations
“…The results of these two experiments clearly supported our hypothesis that the reaction proceeded through radical-radical coupling and not through the radical addition to the double bond of a non-radical substrate. These results were in accordance with most of the literature reports [8,9] and not with the hypothesis suggested by Penning and co-workers, who proposed a mechanism in which the resveratrol dimerization occurs via radical attack to a second molecule of resveratrol. [14] …”
Section: Substrate (Mg)supporting
confidence: 92%
“…[7] More recently, Sako described the non-enzymatic synthesis of 2 involving the treatment of 1 with AgOAc and other metallic oxidants. [8] Similarly, Takaya and co-workers described FULL PAPERS the treatment of 1 with several oxidizing reagents and found that TlA C H T U N G T R E N N U N G (NO 3 ) 3 and K 3 [Fe(CN) 6 ] were the best oxidants to transform 1 into 3, whereas FeCl 3 in acetone and MnO 2 in dichloromethane were the best catalysts to produce the dimer 2. [9] Different studies have shown that resveratrol is transformed in vivo (for instance by incubating 1 with Botrytis cinerea cultures) into various oxidized products (dimers), such as 2.…”
Section: Trans-resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] Typically, mixtures of compounds were observed [6][7][8] and, in those rare instances when selectivity was achieved, solely nonnatural products resulted. [9,10] Thus far, only a highly engineered resveratrol fragment has proven capable of leading to an actual dimeric natural product within this class. [11] Given this state of affairs, we wondered if a structural solution might exist for this general chemoselectivity problem, one empowered by the identification of hidden relationships between their seemingly divergent architectures.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Recently 2,3-dihydrobenzofuran-5-ol has been shown to be more promising than vitamin E2 in inhibition of lipid per oxidation. 7 This skeleton has been a part of number of naturally occurring oxygen heterocycles.…”
Section: Introductionmentioning
confidence: 99%